2020
DOI: 10.3389/fpsyg.2020.572521
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Victimization and Non-suicidal Self-Injurious Behavior Among Chinese Adolescents: School Engagement as a Mediator and Sensation Seeking as a Moderator

Abstract: Although a large body of research has indicated that cyberbullying victimization is a crucial risk factor for adolescent non-suicidal self-injury (NSSI) behavior, the mediating and moderating mechanisms underlying this relationship remain unclear. To address this research gap, this study, based on the social control theory and the organismenvironment interaction model, was designed to test whether school engagement mediated the relationship between cyberbullying victimization and adolescent NSSI and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
7
21
0
Order By: Relevance
“…Thus, adolescents are more strongly influenced by peers, regardless of the level of sensation seeking. This result supports the view that peers have a crucial impact on adolescent development [22,32,48].…”
Section: The Moderating Role Of Sensation Seekingsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, adolescents are more strongly influenced by peers, regardless of the level of sensation seeking. This result supports the view that peers have a crucial impact on adolescent development [22,32,48].…”
Section: The Moderating Role Of Sensation Seekingsupporting
confidence: 87%
“…To be specific, high levels of sensation seeking significantly amplified the impact of depression on adolescent NSSI. These findings were in alignment with a prior study that found that sensation seeking magnified the association between a risk factor (cyberbullying victimization) and adolescent NSSI [32]. According to the sensation seeking theory [49,50], individuals who seek high sensation also tend to enjoy novel experiences and taking risks, which in turn increases the possibility that they will use a risky behavior such as NSSI to escape depression [51].…”
Section: The Moderating Role Of Sensation Seekingsupporting
confidence: 87%
See 3 more Smart Citations